CBSA Approach in Learning Indonesian Language and Literature for Students with Special Needs - Gede Weda Rukmana (Universitas Pendidikan Ganesha, 2024)
The CBSA (Contextual, Based on Students' Ability) approach is used in learning the Indonesian language and literature for students with special needs. This is a CBSA approach to learning Indonesian Language and Literature for students with special needs. The type of research is qualitative research. This method involves collecting data through interviews, observations, or case studies—an analysis technique using qualitative analysis. The research results show that the CBSA approach emphasizes the context and students' ability to understand and use Indonesian. Teachers who implement this approach pay attention to the diversity of student abilities, including students with learning disorders, communication disorders, or other special educational needs. Teachers use strategies and methods tailored to student's needs and skills so that students can learn effectively. In the CBSA approach, teachers use the context of students' daily lives as a basis for learning. Teachers relate learning material to real situations that are relevant to students. This research concludes that the CBSA approach to learning Indonesian Language and Literature can be applied to students with special needs. This research implies that learning Indonesian Language and Literature can be inclusive, meet the needs of students with special needs, and help them reach their full potential in understanding and appreciating Indonesian language and literature.